A Model of the Tactics Used between The Turkish Government and The Kurds in The 2007 - 2012 Peace Process. - Reza Rezeki (HI 14 UMY 028, 2014)
This thesis will explain and seek the explanation and explore the tactics in the conflict of the Kurds under Partiya Kurdistan Karkaren or PKK and the Turkish Government. The conflict of the Turkish Government and the Kurds is caused by differences of interest and the use of different tactics by both conflicting parties. From the Kurds side representative by the PKK and the Turkish Government represent all elements of government. Furthermore, the tactics adopted by both conflicting parties are aimed at obtaining their goals and primary interests. The Turkish Government applied the ideology of the â€œIntegrity of the Nationsâ€, and insisted on maintaining the Kurdish people and the territory in South-eastern Turkey. Meanwhile, the Kurds insisted to separate from the Republic of Turkey region and established new independence states for the Kurdish ethnic group. Keywords: The Kurds, Partiya Kurdistan Karkaren (PKK), the Turkish Government, Separatist group, Conflict, Ethnic groups, Tactics, the Republic of Turkey.